Crosslinguistic Sharing of Morphological Awareness in Biliteracy Development: A Systematic Review and Meta‐Analysis of Correlation Coefficients. Issue 1 (2nd September 2020) - Ke, Sihui (Echo); Miller, Ryan T.; Zhang, Dongbo; Koda, Keiko
Abstract: This study examined the crosslinguistic sharing of morphological awareness (MA) in biliteracy development. The analysis included 34 correlational studies with 41 independent samples ( N = 4, 104). Correlational coefficients were meta‐analyzed, yielding four main findings: (a) the correlation between first language (L1) and second language (L2) MA was small ( r = .30); (b) the interlingual correlations between L1 MA and L2 word decoding and between L1 MA and L2 reading comprehension were both small ( r = .35, .39, respectively); (c) the intralingual correlations between L2 MA and L2 word decoding and between L2 MA and L2 reading comprehension were both moderate ( r = .46, .52, respectively); and (d) MA measurement type and age were significant moderators. Our review suggests that there is a need for future research to align the definition and measurement of MA. Abstract :